Dampak Motivasi Kerja Dan Kompetensi Terhadap Kinerja Pegawai ASN Dan Non ASN Di PDAM Tirta Langkisau (PAINAN) - Zusmawati Zusmawati; Vhani Febrina (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The purpose of this study was to examine the impact of work motivation variables on employee performance at PDAM Tirta Langkisau. to examine the impact of competency variables on employee performance at PDAM Tirta Langkisau. Collecting data by distributing questionnaires to 50 respondents using saturated sampling technique, in which all members of the population are sampled, using instrument testing (validity test and reliability test), descriptive analysis, classic assumption test (normality test, multicollinearity test and heteroscedasticity test) multiple linear regression and t test, with the help of the SPSS application. The results of the study show that work motivation has a positive and significant effect on employee performance at PDAM Tirta Langkisau, competence has a positive and significant effect on employee performance at PDAM Tirta Langkisau. Which means the first hypothesis is accepted and the second hypothesis is accepted.